Causes of death in people with coeliac disease in England compared with the general population: a competing risk analysis - Abdul Sultan, Alyshah; Crooks, Colin J.; Card, Timothy R.; Tata, Laila J.; Fleming, Kate M.; West, Joe (BMJ Publishing Group, 2015)
INTRODUCTION: Quantifying excess cause-specific mortality among people with coeliac disease (CD) compared with the general population accounting for competing risks will allow accurate information to be given on risk of death from specific causes.